A STUDY ON VITREOUS HUMOR BETWEEN-EYE DIFFERENCES AND BASELINE VALUES OF POTASSIUM, CALCIUM, SODIUM AND GLUCOSE IMMEDIATELY AFTER DEATH IN DOGS - S.G. Chavhan; C. Balachandran; A.P. Nambi; G. Dhinakar Raj; S. Vairamuthu (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The present study was conducted to study the vitreous humor between eye differences and baseline values of potassium, sodium, calcium and glucose immediately after death in dogs. Eight canine carcasses brought for necropsy formed the material for collection of vitreous humour in the present study. The information regarding time of death was gathered from dog owners, clinicians and clinical records. Eyes were enucleated as soon as possible after receiving carcass for postmortem. Sampling of vitreous humor was done using 16 gauge needle and 20 ml syringe. The needle was inserted at the lateral angle of eyeball so that the tip of needle was placed at the center of the eyeball. About 50 µL vitreous humour was gently aspirated from each eye and transferred to eppendorf tubes. Sampling of vitreous humour was done within 1-4 hours after death. The aspirated vitreous humour samples were centrifuged at 13,000 rpm for 15 min at 50C temperature and the supernatant was used for analysis. The average vitreous humour concentrations of potassium, sodium, calcium and glucose estimated within 1-4 hours after death were 8.18±0.31 mEq/L, 152.55±4.46 mEq/L, 9.52  ±0.20 mg/dL and 21.70±4.50 mg/dL respectively. The results of this study indicated that there were no significant differences between left and right eye  for all of the vitreous biochemical constituents that were studied in present study (estimated within 1-4 hours after death).